Maternal neglect alters reward-anticipatory behavior, social status stability, and reward circuit activation in adult male rats - Ryakiotakis, Ermis; Fousfouka, Dimitra; Stamatakis, Antonios (Frontiers in Neuroscience, 2023)
Adverse early life experiences affect neuronal growth and maturation of reward circuits that modify behavior under reward predicting conditions. Previous studies demonstrate that rats undergoing denial of expected reward in the form of maternal contact (DER-animal model of maternal neglect) during early post-natal life developed anhedonia, aggressive play-fight behaviors and aberrant prefrontal cortex structure and neurochemistry. Although many studies revealed social deficiency following early-life stress most reports focus on individual animal tasks. Thus, attention needs to be given on the social effects during group tasks in animals afflicted by early life adversity. To investigate the potential impact of the DER experience on the manifestation of behavioral responses induced by natural rewards, we evaluated: 1) naïve adult male sexual preference and performance, and 2) anticipatory behavior during a group 2-phase food anticipation learning task composed of a context-dependent and a cue-dependent learning period. DER rats efficiently spent time in the vicinity of and initiated sexual intercourse with receptive females suggesting an intact sexual reward motivation and consummation. Interestingly, during the context-dependent phase of food anticipation training, DER rats displayed a modified exploratory activity and a markedly decreased overall reward-context association. Moreover, during the cue-dependent phase DER rats displayed a mild deficit in context-reward association while increased cue-dependent locomotion. Additionally, DER rats displayed unstable food access priority following food presentation. These abnormal behaviours were accompanied by overactivation of the ventral prefrontal cortex and nucleus accumbens, as assessed by pCREB levels. Collectively, these data show that the neonatal DER experience resulted in adulthood in altered activation of the reward circuitry and interfered with the normal formation of context-reward associations. These findings provide additional evidence to the deleterious effects of early life adversity on reward system, social hierarchy formation, and brain function.